2018
DOI: 10.1056/nejmc1716477
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic Treatment in Heart Failure

Abstract: The review article by Ellison and Felker (Nov. 16 issue) 1 has a two-edged potential. Physicians are encouraged to use diuretics as first-line therapy for heart failure, but discontent with the drugs runs like a thread through the review. We had hoped that the section on other approaches and future directions would address how to minimize the use of diuretics. Long-term use of diuretic therapy for chronic heart failure may contribute to neurohumoral stimulation. 2 Therefore, not only does skillful use of diure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…NHE3 is the major Na þ transporter in the proximal tubule (48), and genetic deletion of NHE3 from the proximal tubule causes hypotension and salt wasting (49). NKCC2, expressed in the TAL of the loop of Henle, is the molecular target for furosemide (50), an important diuretic agent used in the treatment of hypertension and heart failure (51)(52)(53)(54)(55). Indeed, we showed that diuretic and natriuretic responses to furosemide were significantly attenuated in SMKO animals, consistent with reduced Figure 5.…”
Section: Discussionsupporting
confidence: 67%
“…NHE3 is the major Na þ transporter in the proximal tubule (48), and genetic deletion of NHE3 from the proximal tubule causes hypotension and salt wasting (49). NKCC2, expressed in the TAL of the loop of Henle, is the molecular target for furosemide (50), an important diuretic agent used in the treatment of hypertension and heart failure (51)(52)(53)(54)(55). Indeed, we showed that diuretic and natriuretic responses to furosemide were significantly attenuated in SMKO animals, consistent with reduced Figure 5.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the Diuretic Optimization Strategies Evaluation trial showed that high-dose diuretics might be associated with worsening renal function [ 13 ]. The lack of demonstrated benefit for high-dose diuretics may be related to stimulation of the renin–angiotensin–aldosterone and sympathetic nervous systems [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of CHF includes medical treatment with renin-angiotensin system blockers, beta blockers, and di- ≤60 uretics [28,29]. Because the pathophysiologic mechanisms of cardiorenal syndrome, involving AKI and AHF, are explained mostly by volume congestion [30][31][32], furosemide is one of the standard medications for managing volume congestion in AHF, and has been suggested to improve prognosis in AHF [33][34][35]. One study in patients with AKI suggested that furosemide reduced 2-month mortality when it was appropriately used for volume management [36].…”
Section: Discussionmentioning
confidence: 99%